Performance Analysis of Software-Defined Networking in Band Controllers for Different Network Topologies - Al-Gubouri, Hussein Ali (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2024)
With the great increase in the complexity of networking, software-defined networks have been developed to help administrators operate and configure network services with controllers such as Pox, Ryu, Floodlight and OpenDaylight. Those controllers offer an appropriate platform for applications that need high bandwidth. In this paper, several SDN controllers have been evaluated using in-band communication mode with different network topologies to check the performance of the in-band controllers. Some controllers cannot operate with an in-band controller such as Pox. The controllers were evaluated with Mininet by using iperf and ping networking tools, the packet latency round trip time RTT and the comparison of the throughput of the three topologies. The results of the experiments showed that in-band controllers can be implemented and have efficient results. Results showed that OpenDaylight has the lower value of RTT so it is the best for the applications that need fast response. Ryu has a greater bandwidth value, so it is the best for applications that need high bandwidth. Floodlight comes third in order, after OpenDaylight and Ryu, respectively.